2013
DOI: 10.3389/fendo.2012.00183
|View full text |Cite
|
Sign up to set email alerts
|

Bone circulatory disturbances in the development of spontaneous bacterial chondronecrosis with osteomyelitis: a translational model for the pathogenesis of femoral head necrosis

Abstract: This review provides a comprehensive overview of the vascularization of the avian growth plate and its subsequent role in the pathogenesis of bacterial chondronecrosis with osteomyelitis (BCO, femoral head necrosis). BCO sporadically causes high incidences of lameness in rapidly growing broiler (meat-type) chickens. BCO is believed to be initiated by micro-trauma to poorly mineralized columns of cartilage cells in the proximal growth plates of the leg bones, followed by colonization by hematogenously distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
116
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 137 publications
(359 reference statements)
11
116
0
1
Order By: Relevance
“…Lesions associated with BCO can occur in all bones but are most commonly found in regions of the leg bones that have the widest growth plates and are subjected to torque and stress, such as the proximal tibiotarsus (tibia) and proximal head of the femur (Nairn, 1973;Wideman and Prisby, 2013). The pathogenesis of BCO is thought to be initiated by mechanical damage (e.g., osteochondrosis) to poorly mineralized columns of chondrocytes (cartilage cells) in the epiphyseal and physeal growth plates, followed by colonization of osteochondrotic clefts by hematogenously distributed opportunistic bacteria (Wise, 1971;Nairn, 1973;Howlett, 1980;Mutalib et al, 1983a;Thorp and Duff, 1988;Wideman and Prisby, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions associated with BCO can occur in all bones but are most commonly found in regions of the leg bones that have the widest growth plates and are subjected to torque and stress, such as the proximal tibiotarsus (tibia) and proximal head of the femur (Nairn, 1973;Wideman and Prisby, 2013). The pathogenesis of BCO is thought to be initiated by mechanical damage (e.g., osteochondrosis) to poorly mineralized columns of chondrocytes (cartilage cells) in the epiphyseal and physeal growth plates, followed by colonization of osteochondrotic clefts by hematogenously distributed opportunistic bacteria (Wise, 1971;Nairn, 1973;Howlett, 1980;Mutalib et al, 1983a;Thorp and Duff, 1988;Wideman and Prisby, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of BCO is thought to be initiated by mechanical damage (e.g., osteochondrosis) to poorly mineralized columns of chondrocytes (cartilage cells) in the epiphyseal and physeal growth plates, followed by colonization of osteochondrotic clefts by hematogenously distributed opportunistic bacteria (Wise, 1971;Nairn, 1973;Howlett, 1980;Mutalib et al, 1983a;Thorp and Duff, 1988;Wideman and Prisby, 2013). Numerous bacterial species, including Staphylococcus spp., Escherichia coli, Mycobacterium avium, Salmonella spp., and Enterococcus spp., have been isolated from BCO lesions, with Staphylococcus aureus being routinely isolated over the course of several decades and across broad geographic distributions (Bradshaw et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] On the other hand, in situations with bacteriemia, hematogenously distributed bacteria possessing the specific ability to bind to bone collagen and, has capacity to trigger osteomyelitis. [24,25] The bacteria adhere directly to the cartilage matrix and they form obstructive emboli in the metaphyseal vasculature causes local ischemia and necrosis. [24][25][26] In our patient uncontrolled biliary system infection may possibly lead to osteonecrosis and osteomyelitis as a result of hematogenous dissemination of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] The bacteria adhere directly to the cartilage matrix and they form obstructive emboli in the metaphyseal vasculature causes local ischemia and necrosis. [24][25][26] In our patient uncontrolled biliary system infection may possibly lead to osteonecrosis and osteomyelitis as a result of hematogenous dissemination of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Its essence is death of bone cells in the complicated fractures, which can lead to the changes in bone, cause collapse of the bone fracture, and change the shape and function. Many studies have shown that one of the important factors causing bone cell apoptosis is blood supply to the femoral head [6][7][8]. Non-traumatic femoral head necrosis is divided into ischemic and idiopathic necrosis of the femoral head [9][10][11].…”
Section: Introductionmentioning
confidence: 99%